12+8x-4=5+2(3x-1)

Simple and best practice solution for 12+8x-4=5+2(3x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12+8x-4=5+2(3x-1) equation:


Simplifying
12 + 8x + -4 = 5 + 2(3x + -1)

Reorder the terms:
12 + -4 + 8x = 5 + 2(3x + -1)

Combine like terms: 12 + -4 = 8
8 + 8x = 5 + 2(3x + -1)

Reorder the terms:
8 + 8x = 5 + 2(-1 + 3x)
8 + 8x = 5 + (-1 * 2 + 3x * 2)
8 + 8x = 5 + (-2 + 6x)

Combine like terms: 5 + -2 = 3
8 + 8x = 3 + 6x

Solving
8 + 8x = 3 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
8 + 8x + -6x = 3 + 6x + -6x

Combine like terms: 8x + -6x = 2x
8 + 2x = 3 + 6x + -6x

Combine like terms: 6x + -6x = 0
8 + 2x = 3 + 0
8 + 2x = 3

Add '-8' to each side of the equation.
8 + -8 + 2x = 3 + -8

Combine like terms: 8 + -8 = 0
0 + 2x = 3 + -8
2x = 3 + -8

Combine like terms: 3 + -8 = -5
2x = -5

Divide each side by '2'.
x = -2.5

Simplifying
x = -2.5

See similar equations:

| 4x+8x+150=164 | | 16(x-2)2-25=0 | | 3(2x+3)=11x+8-5x+1 | | 1x^2+17x+16=0 | | -3-3(8c+7)= | | -8.3x-4.5y+3.4x+3.7y= | | 48=3(2)x | | v-2.9=10.44(46.16568) | | -8=6(x-8) | | 4x-4=-2x+5 | | 4w^2-15w-9=0 | | X^2-1.4x+0.49=0 | | -0.7r-2.1+5.8r-12.8= | | b=2c^2+3c | | x+y+2x=180 | | 3y=127+60 | | 14=7(x+4) | | 250+150(26)=x | | 250+150=26 | | (5)-(9)= | | 3+5(5)=c | | 18=m(3)+b | | 11+w=-7 | | 2-3x=40-x-x+10 | | 4x-2=-1+8 | | -2+48= | | -4(x-8)=12x+32+8x | | -8=1/2x-3 | | 7(x-3)=70 | | 2y-2x=-6 | | 2(10+.25y)+3y=34 | | 4m+yr=r-9h |

Equations solver categories